Landscape Of Desire - Gordon, Greg (University Press of Colorado, 2003)
Landscape of Desire powerfully documents and celebrates a place and the evolutions that occur when human beings are intimately connected to their surroundings. Greg Gordon accomplishes this with a tapestry of writing that interweaves land use history, natural history, experiential education, and personal reflection. He tracks the geomorphology of southern Utah as well as the creatures and plants his student group encounters, the history lessons (planned and unplanned), the trials and joys of gathering so many individuals into a cohesive will, and his own personal epiphanies, restraints, insights, and disillusionments. Landscape of Desire examines the plight of the western landscape. It discusses a wide range of issues, including mining, grazing, dams, recreation, wilderness, and land management. Since recreation has replaced extraction industries as the primary use of wilderness, especially in southern Utah, Gordon addresses its impactful qualities. He overviews the history of the conflict between preservation and development and places these issues in a cultural context. The text is presented in a narrative format, following the individuals of one field course Gordon lead that explored Muddy Creek and the Dirty Devil River from Interstate 70 to Lake Powell. Though each chapter focuses on the geologic formation the group is traveling through, the plants, animals, ecology, and human impacts are all tightly woven into the narrative. Not only does the land affect the members of the field course, but their attitudes and insights affect the land. In Landscape of Desire Gordon achieves a vision of wholeness of this popular and contested region of Utah that centers around the implications of being human and also stewards of the wild.